Haji dan Pengembangan Sikap Egaliter ( Kajian Sosiologi ) - Nur Dzaedzatul H; Syamsurizal Yazid (Moral : Jurnal kajian Pendidikan Islam, 2025)
The aim of this research is to explore the implementation of the Hajj pilgrimage in the development of an egiliterary attitude which is studied from a sociological perspective. This research uses a qualitative approach with a library study type of research. The data sources used were the Al Qur'an and Hadith, as well as books and journals related to the theme of Hajj and the development of egalitarian attitudes. The results of this research show that several developments were found in the formation of egalitarian attitudes after carrying out the Hajj in society. The Hajj pilgrimage, which is one of the pillars of Islam, brings together Muslims from various social, economic and cultural backgrounds in the Holy Land. The process of carrying out the Hajj which involves certain rituals, such as Tawaf and Sa'i, teaches the values of simplicity and sincerity. All pilgrims, regardless of social status, wear the same ihram clothing, symbolic of the elimination of differences. This encourages individuals to internalize the principles of egalitarianism, eliminate discriminatory traits, and strengthen solidarity.